The Effect Of Intrasocket Reactive Tissue On Alveolar Ridge Preservateion - Yuanyuan, Wang (International dental journal, 2025)
The current study aims to evaluate the efficacy of intrasocket reactive tissue for alveolar ridge preservation after extraction in severe periodontal defects. A total of 61 sites were included into this study, which were divided into group 1 with 31 sites: conventional GBR method (bio-oss bone powder + bio-gide collagen membrane); group 2 with 11 cases: using bio-oss bone graft alone; and group 3 with 19 sites: using bio-oss -oss bone graft combined with intrasocket reactive tissue. The CBCT images of patients immediately after site preservation (T1) and 4-6 months after surgery (T2) were measured to analyze the alveolar bone volume changes in the height and width in each group. The mesial height, middle height, buccal height, lingual height and average height of alveolar bone in group 3 were significantly lower than those in group 1 (P<0,05). The intrasocket reactive tissue has better alveolar ridge preservation effect than the conventional GBR method in the vertical bone maintenance. And there was no significant difference in alveolar with changes, new bone quality and alveolar crest morphology between intrasocket reactive tissue and conventional alveolar ridge preservation methods.